2022
DOI: 10.3389/fnagi.2022.923720
|View full text |Cite
|
Sign up to set email alerts
|

White matter hyperintensities in Burning Mouth Syndrome assessed according to the Age-Related White Matter Changes scale

Abstract: BackgroundWhite matter hyperintensities (WMHs) of the brain are observed in normal aging, in various subtypes of dementia and in chronic pain, playing a crucial role in pain processing. The aim of the study has been to assess the WMHs in Burning Mouth Syndrome (BMS) patients by means of the Age-Related White Matter Changes scale (ARWMCs) and to analyze their predictors.MethodsOne hundred BMS patients were prospectively recruited and underwent magnetic resonance imaging (MRI) of the brain. Their ARWMCs scores w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 82 publications
0
14
0
Order By: Relevance
“…The impact of long-term elevated blood pressure on cerebral health involves structural pathological changes of the brain such as WMH, cortical thinning, enlarged Virchow-Robin spaces, and brain atrophy (67), suggesting that HTN can accelerate brain aging in the same areas involved in chronic pain. However, it is difficult to determine if these brain alterations are a direct consequence of HTN but it could explain the previous study results in which a high prevalence of WMH was found in patients with BMS (68,69).…”
Section: Discussionmentioning
confidence: 86%
“…The impact of long-term elevated blood pressure on cerebral health involves structural pathological changes of the brain such as WMH, cortical thinning, enlarged Virchow-Robin spaces, and brain atrophy (67), suggesting that HTN can accelerate brain aging in the same areas involved in chronic pain. However, it is difficult to determine if these brain alterations are a direct consequence of HTN but it could explain the previous study results in which a high prevalence of WMH was found in patients with BMS (68,69).…”
Section: Discussionmentioning
confidence: 86%
“…This sample size was obtained using the effect size value equal to 0.65, measured in a previously published research study regarding the ARWMCs. [25] The calculations were computed using the GPower software (v 3.1.9). Data analyses were performed using the R software (v. 4.2.0 -R Core Team, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…[44] Moreover, this high prevalence of WMCs in the brain of patients with BMS has been further confirmed in a more extensive study suggesting a potential role of cardiovascular risk factors, especially HTN, in the brain's aging and subsequently in aggravating the disease. [25] Until now, the role of comorbidities in BMS has been poorly studied and understood but in a recent study de Pedro et al have reported that BMS patients suffered from worsened health status, consuming more medications with a worse general quality of life, need an interdisciplinary therapy approach. [8] Therefore, the primary outcome of this study has been to establish if there is any difference in terms of the prevalence of the one of the most common medical comorbidities such as HTN between BMS patients and control subjects in order to confirm these previous studies findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The aetiopathogenesis of this disease is complex and may be multifactorial, as local, systemic, and psychological factors are considered to be involved in generating symptoms. A recent publication points to the idea that enhanced pain perception in BMS could be linked to a higher frequency of white matter hyperintensities (WMHs) in the brain [ 28 ]. The literature indicates that psychotherapy and behavioral feedback may help to eliminate BMS symptoms [ 29 ].…”
mentioning
confidence: 99%